Integrative molecular characterization of pediatric spinal ependymoma: the UK Children's Cancer and Leukaemia Group study. Issue 1 (8th March 2021) - Ahmad, Omar; Chapman, Rebecca; Storer, Lisa C; Luo, Li; Heath, Paul R; Resar, Linda; Cohen, Kenneth J; Grundy, Richard G; Lourdusamy, Anbarasu
Abstract: Background: Pediatric spinal ependymomas (SP-EPNs) are rare primary central nervous system tumors with heterogeneous clinical course. Considering that ependymomas in children are biologically distinct from their adult counterparts, this study aimed to define the molecular landscape of SP-EPNs in children. Methods: In this retrospective study, we have collected tumor samples from 27 SP-EPN patients younger than 18 years and carried out the histological review, DNA methylation, and gene expression profiling. Results: Unsupervised analyses with methylation profiles revealed 2 subgroups where all grade I tumors ( n = 11) were in Group 1, but the grade II/III tumors split into 2 groups ( n = 7 in Group 1 and n = 9 in Group 2). The Heidelberg classifier assigned Group 1 tumors as spinal myxopapillary ependymomas (SP-MPEs), 5 Group 2 tumors as SP-EPNs, and failed to classify 4 Group 2 tumors. Copy numbers derived from DNA methylation arrays revealed subgroup-specific genetic alterations and showed that SP-EPN tumors lack MYCN amplification. Gene expression profiling revealed distinct transcriptomic signatures, including overexpression of genes involved in oxidative phosphorylation in SP-MPEs that were validated by Western blot analysis. We discovered widespread decreases in DNA methylation at enhancer regions that are associated with the expression of oncogenic signaling pathways in SP-MPEs. Furthermore, transcription factor motifs for master regulators, including HNF1B, PAX3, and ZIC3, were significantly overrepresented in probes specific to distal regulatory regions in SP-MPEs. Conclusion: Our findings show substantial heterogeneity in pediatric SP-EPN and uncover novel enhancers and transcriptional pathways specific to the SP-MPE subgroup, providing a foundation for future therapeutic strategies.